Derecho a la ciudad en contextos mineros: la lucha de las mujeres en La Rinconada, Puno, Perú - Quispe Puente, Maria Teresa (Pontificia Universidad Católica del Perú, 2025)
Informal mining in the Peruvian highlands, particularly in La Rinconada, Puno, Peru, shapes an urban environment that reinforces the exclusion of women from public spaces. This article uses a right-to-the-city approach and gender-sensitive urbanism to analyze how the spatial configuration of the city -characterized by precarity and the absence of the state- limits women’s access to essential services, safety, and participation. Based on participant observation and interviews, the research shows how informal mining dynamics and structural violence restrict women’s mobility and relegate them to subordinate roles within the community. Despite this hostile context, the article suggests that transformation is possible through self-organization, community mobilization, and the recognition of care work. Drawing on examples of women’s collectives in other Latin American cities, it argues that in La Rinconada, women can redefine their relationship with urban space, claim their right to the city, and contribute actively to building a more just, inclusive, and equitable urban environment.

La minería informal en el altiplano peruano, específicamente en La Rinconada, Puno, Perú, configura un entorno urbano que refuerza la exclusión de las mujeres en los espacios públicos. Este artículo utiliza un enfoque de derecho a la ciudad y el urbanismo con perspectiva de género para analizar cómo la distribución espacial de la ciudad, marcada por la precariedad y la ausencia estatal, limita el acceso de las mujeres a servicios esenciales, seguridad y participación. Mediante la observación participante y entrevistas, se muestra cómo las dinámicas de la minería informal y la violencia estructural dificultan la movilidad y relegan a las mujeres a posiciones subalternas dentro de la comunidad. A pesar de este contexto hostil, el artículo plantea la posibilidad de transformación mediante la autogestión, la organización comunitaria y el reconocimiento de los trabajos de cuidado. Tomando ejemplos de colectivos de mujeres en otras ciudades latinoamericanas, se propone que en La Rinconada las mujeres pueden redefinir su relación con el espacio urbano, ejercer su derecho a la ciudad y contribuir activamente a la construcción de una ciudad más justa, inclusiva y equitativa.
Right to the City in Mining Contexts: The Struggle of Women in La Rinconada
Keywords: Informal mining; Right to the city; Gender and urban space; Community self-management; Minería informal; Derecho a la ciudad; Género y espacio urbano; Auto-gestión comunitaria; https://purl.org/pe-repo/ocde/ford#6.04.08